Development of fully dense and high performance powder metallurgy HSLA steel using HIP method. (23rd May 2018) - Liu, Wensheng; Pang, Xinkuan; Ma, Yunzhu; Cai, Qingshan; Zhu, Wentan; Liang, Chaoping
Abstract: In order to solve the problem that the mechanical properties of powder metallurgy (P/M) steels are much lower than those of traditional cast steels with the same composition due to their porosity, a high–strength–low–alloy (HSLA) steel with fully dense and excellent mechanical properties was fabricated through hot isostatic pressing (HIP) using gas–atomized powders. The granular structure in the P/M HIPed steel composed of bainitic ferrite and martensite–austenite (M–A) islands is obtained without the need of any rapid cooling. The P/M HIPed steel exhibit a combination of tensile strength and ductility that surpasses that of conventional cast steel and P/M sintered steel, confirming the feasibility of fabricating high performance P/M steel through appropriate microstructural control and manufacture process.